Transient perivascular inflammation of the carotid artery syndrome in a 52-year-old female patient: a case report - Christos Dimopoulos; Sotirios Bisdas; Theodosios Bisdas (Journal of Medical Case Reports)
Abstract Background Transient perivascular inflammation of the carotid artery syndrome is a rare and under-recognized clinical condition. It may mimic more serious vascular disorders such as carotid dissection or vasculitis, leading to unnecessary investigations or treatment. Recognition of this benign, self-limiting entity is essential to ensure appropriate management. Case presentation We describe the case of a 52-year-old Caucasian Greek woman who presented with acute, well-localized pain on the left side of her neck, centered over the carotid artery and radiating toward the ipsilateral jaw. She had no systemic or neurological symptoms. Physical examination revealed focal tenderness over the left carotid bifurcation. Initial Doppler ultrasound raised suspicion of carotid artery dissection; however, magnetic resonance imaging demonstrated eccentric wall thickening and perivascular fat stranding without luminal narrowing or enhancement, findings consistent with transient perivascular inflammation of the carotid artery syndrome. The differential diagnosis included dissection, vasculitis, and lymphadenopathy, all excluded by clinical and imaging evaluation. The patient was managed conservatively with nonsteroidal antiinflammatory drugs, resulting in complete resolution of symptoms within 4 weeks. Follow-up magnetic resonance imaging at 6 months confirmed no recurrence. Conclusion This case highlights the importance of considering transient perivascular inflammation of the carotid artery syndrome in patients presenting with localized neck pain and suggestive imaging features. Accurate diagnosis can help avoid unnecessary interventions and promote effective, conservative treatment.